2017
DOI: 10.1038/srep46127
|View full text |Cite
|
Sign up to set email alerts
|

An endemic rat species complex is evidence of moderate environmental changes in the terrestrial biodiversity centre of China through the late Quaternary

Abstract: The underlying mechanisms that allow the Hengduan Mountains (HDM), the terrestrial biodiversity centre of China, to harbour high levels of species diversity remain poorly understood. Here, we sought to explore the biogeographic history of the endemic rat, Niviventer andersoni species complex (NASC), and to understand the long-term persistence of high species diversity in this region. In contrast to previous studies that have proposed regional refuges in eastern or southern of the HDM and emphasized the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 94 publications
(117 reference statements)
0
12
1
Order By: Relevance
“…In these areas, the young uplifting plateau (Tibetan Plateau), the old eastern escarpment and the southeast slope (Hengduan Mountains) yield highly heterogeneous habitats not only to ‘living fossil’ species, such as the Laotian rock rat Laonastes aenigmamus [61] but also to some new speciated species, for example Apodemus ilex [62]. Besides the species level diversity, high intraspecific genetic diversity of some species in these areas was also frequently reported [63, 64] because these areas were refuges for different species during glacial periods. According to Musser and Carleton [65], R. tanezumi is indigenous to the north of the India subcontinent, South and Central China, and mainland Indochina in which Yunnan is the central area.…”
Section: Discussionmentioning
confidence: 99%
“…In these areas, the young uplifting plateau (Tibetan Plateau), the old eastern escarpment and the southeast slope (Hengduan Mountains) yield highly heterogeneous habitats not only to ‘living fossil’ species, such as the Laotian rock rat Laonastes aenigmamus [61] but also to some new speciated species, for example Apodemus ilex [62]. Besides the species level diversity, high intraspecific genetic diversity of some species in these areas was also frequently reported [63, 64] because these areas were refuges for different species during glacial periods. According to Musser and Carleton [65], R. tanezumi is indigenous to the north of the India subcontinent, South and Central China, and mainland Indochina in which Yunnan is the central area.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the current distribution ranges of species of the H. martynovi -complex and our knowledge on range displacement during climate oscillations for organisms of the Hengduan Mts, we hypothesize that our results match with a general species-pump scenario. For example, it is often reported that species or populations have diverged allopatrically in the northern and southern Hengduan Mts, respectively [ 15 , 62 , 63 ]. This might have been the case for H. epikur (southern Hengduan Mts) and H. martynovi s.s. (northern Hengduan Mts), since these two species occur in drainage systems that were historically distinct [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Hengduan Mts, climate changes and orogenic movements profoundly changed the relative frequency and the distribution of available habitats, affecting species movement and distributions and ultimately speciation and patterns of diversity [ 13 ]. Species complexes are common in the Hengduan Mts (e.g., plant [ 14 ], mammal [ 15 ], fungus [ 16 ], caddisflies [ 17 ]) and represent good models for studying evolutionary processes and mechanisms of speciation in the context of the mountain-geobiodiversity hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility and the recurrent range fragmentation and contraction caused by Quaternary climatic changes could lead to a largely disjunct distribution. Such a model provides a hypothesis for explaining scattered ranges and can be considered in future studies of the evolutionary histories of frogs and many other organisms isolated in the mountains surrounding the Sichuan Basin [38,39,48,63,64,66,67]. A substantially different modeled LIG distribution compared with those during the present interglacial period is not unique to the Emei mustache toad.…”
Section: Climatic Suitabilitymentioning
confidence: 99%